2015
DOI: 10.1073/pnas.1424017112
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-associated dysregulation of O -GlcNAcylation in rat cardiac mitochondria

Abstract: Elevated mitochondrial O-GlcNAcylation caused by hyperglycemia, as occurs in diabetes, significantly contributes to mitochondrial dysfunction and to diabetic cardiomyopathy. However, little is known about the enzymology of mitochondrial O-GlcNAcylation. Herein, we investigated the enzymes responsible for cycling O-GlcNAc on mitochondrial proteins and studied the mitochondrial transport of UDP-GlcNAc. Analyses of purified rat heart mitochondria from normal and streptozocin-treated diabetic rats show increased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
182
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 32 publications
9
182
1
Order By: Relevance
“…The values are the means ± SEM; n = 4; *p < 0.05; **p < 0.01. siOga, Oga siRNA mitochondrial O-GlcNAcylation was dramatically reduced because of increased mitochondrial OGA levels. This finding is supported by the recent discovery of OGA mitochondrial localisation [25]. In addition to the mitochondrial density affected by OGA deficiency, we also showed that mitochondrial protein O-GlcNAcylation was altered in response to OGA knockdown during myogenesis and in fully differentiated myotubes, and was accompanied by impaired mitochondrial function, including significantly lowered ATP content, increased ROS content and protein and lipid oxidation.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The values are the means ± SEM; n = 4; *p < 0.05; **p < 0.01. siOga, Oga siRNA mitochondrial O-GlcNAcylation was dramatically reduced because of increased mitochondrial OGA levels. This finding is supported by the recent discovery of OGA mitochondrial localisation [25]. In addition to the mitochondrial density affected by OGA deficiency, we also showed that mitochondrial protein O-GlcNAcylation was altered in response to OGA knockdown during myogenesis and in fully differentiated myotubes, and was accompanied by impaired mitochondrial function, including significantly lowered ATP content, increased ROS content and protein and lipid oxidation.…”
Section: Discussionsupporting
confidence: 86%
“…2c). In response to a recent report of localised OGA in mitochondria [25], we analysed the mitochondria and found that mitochondrial OGA levels sharply increased during myogenesis and were accompanied by decreased mitochondrial O-GlcNAcylation (Fig. 2d).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations